Hemodynamic factors affecting the suitability of the donated heart and kidney for transplantation - Nozary Heshmati, B; Ahmadi, F; Azimi, P; Tirgar, N; Barzi, F; Gatmiri, S M (International journal of organ transplantation medicine, 2013)
Due to the loss of autonomic nervous system, precise control of the hemodynamic status in dead brain potential donors presents a clinical dilemma. In these patients, due to head trauma and cerebral edema, fluids administration is restricted. Moreover, the decreased central venous pressure may put the viability of the organs at risk. To investigate hemodynamic factors affecting the suitability of the donated heart and kidney for transplantation. Data were retrospectively collected from the maintained databases of all dead-brain donors (DBDs) admitted to our organ procurement unit (OPU) ICU between 1999 and 2008. In this study, laboratory variables in addition to demographic data were collected. The time between donor entrance to the DBD ICU and organ procurement, vital signs, hourly urine output, amount of IV fluid administered, and the dosage of vasopressor and desmopressin were recorded. The end-point of the study was organ suitability for organ retrieval. A total of 132 dead brain donors were studied. The mean±SD age of the donors was 26.3±12.2 years. The main cause of brain death was multiple trauma (53%). The organ retrieval rate was 82.6% for the kidney, 59.8% for the liver, and 53% for the heart. 83 (63%) and 106 (80.3%) donors had suitable hearts and kidneys, respectively. 66 cases did not receive desmopressin (50.4%) at all. The mean±SD dose of desmopressin the donors received was 7±1 µg. There was a significant association between the suitability of these two organs for transplantation and the dosage of the administered desmopressin and volume of IV solution the donors received. Fluid therapy and administration of desmopressin can improve the number and quality of retrieved organs from dead brain donors.